Venom from Bothrops lanceolatus, a Snake Species Native to Martinique, Potently Activates the Complement System. (15th July 2018) - Delafontaine, Marie; Villas-Boas, Isadora Maria; Pidde, Giselle; van den Berg, Carmen W.; Mathieu, Laurence; Blomet, Joël; Tambourgi, Denise V.
Abstract : Bothrops lanceolatus snake venom causes systemic thrombotic syndrome but also local inflammation involving extensive oedema, pain, and haemorrhage. Systemic thrombotic syndrome may lead to fatal pulmonary embolism and myocardial and cerebral infarction. Here, we investigated the ability of B. lanceolatus venom to activate the Complement system (C) in order to improve the understanding of venom-induced local inflammation. Data presented show that B. lanceolatus venom is able to activate all C-pathways. In human serum, the venom strongly induced the generation of anaphylatoxins, such as C5a and C4a, and the Terminal Complement complex. The venom also induced cleavage of purified human components C3, C4, and C5, with the production of biologically active C5a. Furthermore, the venom enzymatically inactivated the soluble C-regulator and the C1-inhibitor (C1-INH), and significantly increased the expression of bound C-regulators, such as MCP and CD59, on the endothelial cell membrane. Our observations that B. lanceolatus venom activates the three Complement activation pathways, resulting in anaphylatoxins generation, may suggest that this could play an important role in local inflammatory reaction and systemic thrombosis caused by the venom. Inactivation of C1-INH, which is also an important inhibitor of several coagulation proteins, may also contribute to inflammation and thrombosis. Thus, further in vivo studies may support the idea that therapeutic management of systemic B. lanceolatus envenomation could include the use of Complement inhibitors as adjunct therapy.